Status, Prospects, Threats, and the Way Forward for Sustainable Management and Enhancement of the Tropical Indian Reservoir Fisheries: An Overview. Issue 2 (3rd April 2018) - Sarkar, U. K.; Sandhya, K. M.; Mishal, P.; Karnatak, G.; , Lianthuamluaia; Kumari, S.; Panikkar, P.; Palaniswamy, R.; Karthikeyan, M.; Mol, S. Sibina; Paul, T. T.; Ramya, V. L.; et al.
ABSTRACT: The fisheries sector plays a vital role in the food, nutritional and livelihood security of people, especially in the rural regions of India. Reservoirs, the man made impoundments built on rivers/streams obstructing the surface flow, form an important resource for the fish production besides holding up economic growth through various cultural and ecological services. India has enormous reservoir resources to the tune of 3.42 million ha (19, 386 numbers). The distribution of reservoirs is quite uneven and most of the reservoirs are located in the southern and central Indian states. In the last few decades, India has made tremendous progress in reservoir fisheries and overall management strategies have been considerably innovated. The average annual fish productivity realized from reservoirs was very low (small: 49.9, medium: 12.3 and large: 11.4 kg ha −1 yr −1 ) against the annual potential yield of 100, 75, and 50 kg ha −1 yr −1 . The fish yield from Indian reservoirs has enhanced through fingerling stocking and adoption of improved management practices and the average productivity increased to 33, 94, and 174 kg ha −1 yr −1 from large, medium, and small reservoirs respectively. The production potential has been re-casted to a level of 100, 200, and 500 kg ha −1 yr −1 from large, medium and small reservoirs, respectively. The increase in fish productivity is about one third of the present production potential and there exists scope for developing effective and sustainable strategies for further enhancing the fish yield. The present review synthesizes the updated information available on Indian reservoirs and the developments during the last decade with reference to fisheries, biodiversity, potential, threats, and recommends strategies for sustainable management of the reservoir fisheries in India.